Improving Fine Motor Skills through Pattern Cutting Activities in RA At-Taqwa Children - Sulfi Mubarrokah; Ahmad Afandi; A. Zulkarnain Ali (SAINTIS Publishing, 2025)
This study aims to determine the improvement of children's fine motor skills through the implementation of pattern cutting activities at RA At-Taqwa. This study is a Classroom Action Research (CAR) with a descriptive method approach. This research was conducted collaboratively between researchers and class teachers to improve children's fine motor skills through pattern-cutting activities. This study was designed in two cycles, where each cycle consists of four main stages, namely: a) planning; b) implementing action; c) observing; and d) reflecting. The results showed that 11 of the 17 children (64.71%) had achieved the success indicator, which was at least in the Developing According to Expectations (BSH) category. This result did not meet the success indicator, so it will be continued in cycle II. Based on the results of the reflection, the teacher made a number of improvements in cycle II, including simplifying the pattern, adding motor warm-up activities, and providing assistance based on the child's abilities. After these improvements, the results in cycle II showed a significant improvement. A total of 11 children (64.7%) reached the BSB category, 5 children (29.41%) were in the BSH category, and only 1 child (5.88%) was still in the MB category. No children were in the BB category. This means that 16 of the 17 children (94.12%) have achieved the success indicator, which is at least in the Developing According to Expectations (BSH) category.